THE IMPACT OF GLOBALISATION ON THE PRIVATISATION POLICY OF SOME STATE ENTERPRISES IN INDONESIA - Yusa Djuyandi, Ratnia Solihah, Siti Witianti (Hamdard Islamicus, 2020)
Globalisation is considered to have positively impacted some third world countries because it is believed to have the power to improve the life quality of citizens. However, anti-globalisation groups believe that the globalisation wave has made third world countries vulnerable to exploitation. In Indonesia in particular, globalisation has had both positive and negative impacts. One of the negative impacts is the growing global demand for the privatisation of state-owned enterprises. Consequently, this study employs a qualitative method, in which the data is obtained from observations and interviews. In addition, this study employs various secondary data, such as documents and news sources, as a supplement. The results of the study show that globalisation has suppressed the third world countries by weakening the role of the state in controlling the political economy and by giving more power to the market mechanism. In addition, privatisation and free trade system have not freed the third world countries from economic backwardness.